Deployment of Six Sigma Methodology to Reduce Complications in Intravitreal Injections - SAHBAZ, İbrahim and TANER, Mehmet Tolga and ELIACIK, Mustafa and KAGAN, Gamze and ERBAS, Engin and ENGUNYURT, Hazar (International Review of Management and Marketing, 2014)
The purpose of this study is to show how a private eye care center in Turkey initiated Six Sigma principles to reduce the number of complications encountered during and after intravitreal injections. Data were collected for 30-months. To analyse the complications among 229 injections administered on 106 patients, main tools of Six Sigma’s Define-Measure-Analyze-Improve-Control (DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Sources and root causes of seven types of complications were identified and reported. For a successful intravitreal injection, experience of the retina specialist, attention of the retina specialist and patient’s ocular pathology were determined to be the “critical few” factors whereas, sterilization and hygiene, dosage of drug/agent and chemical properties of drug/agent were found to be the “trivial many”factors. The most frequently occuring and the complication with the highest hazard score was found to be subconjunctival haemorrhage. The process sigma level of the process was measured to be 3.2657. The surgical team concluded that six of the complications (out of seven) should be significantly reduced by taking the necessary preventative measures. Keywords: Six Sigma; Ophthalmology; Intravitreal injections; Complications JEL Classifications: I120; L15